2015
DOI: 10.1038/cdd.2015.55
|View full text |Cite
|
Sign up to set email alerts
|

PreImplantation Factor bolsters neuroprotection via modulating Protein Kinase A and Protein Kinase C signaling

Abstract: A synthetic peptide (sPIF) analogous to the mammalian embryo-derived PreImplantation Factor (PIF) enables neuroprotection in rodent models of experimental autoimmune encephalomyelitis and perinatal brain injury. The protective effects have been attributed, in part, to sPIF's ability to inhibit the biogenesis of microRNA let-7, which is released from injured cells during central nervous system (CNS) damage and induces neuronal death. Here, we uncover another novel mechanism of sPIF-mediated neuroprotection. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
80
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(93 citation statements)
references
References 70 publications
11
80
2
Order By: Relevance
“…Notably, IL-18 contributes to preterm birth in part by modulating TLR4 signaling [36] and TLR4 activation is necessary for PIF effects [27, 28]. We focused on NALP-3 and ASC proteins expression in the placenta as these are the key components of inflammasome signaling [4, 5].…”
Section: Resultsmentioning
confidence: 99%
“…Notably, IL-18 contributes to preterm birth in part by modulating TLR4 signaling [36] and TLR4 activation is necessary for PIF effects [27, 28]. We focused on NALP-3 and ASC proteins expression in the placenta as these are the key components of inflammasome signaling [4, 5].…”
Section: Resultsmentioning
confidence: 99%
“…These are in line with observations made in non-pregnant in vivo models. Specifically, in several models of immunity and transplant, PIF led to protection against oxidative stress (Weiss et al, 2011(Weiss et al, , 2012Azar et al, 2013;Shainer et al, 2013;Almogi-Hazan et al, 2014;Mueller et al, 2014Mueller et al, , 2015. In addition, as recently shown, PIF also protects against ionized radiation-induced damage (Shainer et al, 2014).…”
Section: Third Critical Element In Pregnancy Success; Immune Responsementioning
confidence: 87%
“…37 Our results agree with those observed in brain and pancreas, where sPIF has an important role in preventing cell death. 16, 38, 39 In particular, it has recently been reported that the PIF-associated inhibition of the death of mouse neuroblastoma cells is associated with an increase in BCL2 expression and a decrease in microRNA let-7 levels. 38, 39 Hence, the sPIF's neuroprotective effect may be due (at least in part) to its ability to inhibit the release of a microRNA that is specifically produced after central nervous system damage.…”
Section: Discussionmentioning
confidence: 99%